2014
DOI: 10.1590/0004-2730000003097
|View full text |Cite
|
Sign up to set email alerts
|

Redução da mobilidade funcional e da capacidade cognitiva no diabetes melito tipo 2

Abstract: RESUMOObjetivos: Avaliar a mobilidade funcional e sua relação com a capacidade cognitiva em pacientes com diabetes tipo 2 (DM2) entre 50 e 65 anos de idade, e com menos de 10 anos de diagnóstico. Materiais e métodos: Estudo observacional, analítico e transversal envolvendo indiví-duos não diabéticos e pacientes com DM2 com controle glicêmico inadequado, selecionados por amostra de conveniência. Em ambos os grupos, foram aplicados questionário estruturado, avaliação cognitiva com Miniexame do Estado Mental (MEE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
1
7
0
7
Order By: Relevance
“…It should be emphasized that although it is a very objective instrument, it only tracks cognitive deficiencies and should not be used alone to diagnose 11 . The mean MMSE below the cutoff point of the elderly with DM2 corroborated with the main studies in the literature 4,5 .It is important to emphasize that to date, there is no consensus regarding cut-off points for cognitive decline in Brazil. The Brazilian version of the test used by Bertolucci et.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It should be emphasized that although it is a very objective instrument, it only tracks cognitive deficiencies and should not be used alone to diagnose 11 . The mean MMSE below the cutoff point of the elderly with DM2 corroborated with the main studies in the literature 4,5 .It is important to emphasize that to date, there is no consensus regarding cut-off points for cognitive decline in Brazil. The Brazilian version of the test used by Bertolucci et.…”
Section: Discussionsupporting
confidence: 73%
“…In addition to the micro and macrovascular complications that diabetes mellitus can cause, DM2 has been one of the major public health concerns, as evidence indicates a positive relationship between DM2 and cognitive decline. Studies that analyze this association between the prevalence of diabetes and cognitive alterations in the elderly have shown that elderly people with DM2 present worse cognitive performance, suggesting the DM2 as an aggravating factor in the performance of the cognitive capacity in which even without clear pictures of dementia certain cognitive domains such as attention, memory, executive functions and frontal lobe, can be impaired 3,4,5 . The early detection of cognitive alterations contributes directly to the neuropsychological evaluation and the management of pathological cognitive aging, facilitating the therapeutic behavior during the onset of neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…An analytical and observational study developed with a group of diabetics and a control group, observed that when the fall involves people with diabetes mellitus there is higher incidence of cognitive disorders and functional mobility, in addition to worse mobility on those with greater cognitive decline. The worse functional mobility and worse cognitive performance of patients with diabetes can be a result of poor glycemic control, overlapped to other aspects inherent to the disease (25) . Although pain presented no statistical relation in this study, a population survey with older adults without cognitive deficit, residents in the city of São Paulo, Brazil, showed that the risk of falling was greater (48%) among those with pain and urinary incontinence diagnosis, i.e., the association between chronic pain and urinary incontinence significantly increased the chances of falling (26) .…”
Section: Discussionmentioning
confidence: 99%
“…An important consequence of the aging of people with DM2 is physical disability, particularly the loss of mobility [2]. This pathology makes the elderly more susceptible to a gradual and successive decrease in functional capacity and reserves.…”
Section: Introductionmentioning
confidence: 99%